Optimized nitrogen application methods to improve nitrogen use efficiency and nodule nitrogen fixation in a maize-soybean relay intercropping system - Tai-wen YONG; Ping CHEN; Qian DONG; Qing DU; Feng YANG; Xiao-chun WANG; Wei-guo LIU; Wen-yu YANG (Journal of Integrative Agriculture, 2018)
In China, the abuse of chemical nitrogen (N) fertilizer results in decreasing N use efficiency (NUE), wasting resources and causing serious environmental problems. Cereal-legume intercropping is widely used to enhance crop yield and improve resource use efficiency, especially in Southwest China. To optimize N utilization and increase grain yield, we conducted a two-year field experiment with single-factor randomized block designs of a maize-soybean intercropping system (IMS). Three N rates, NN (no nitrogen application), LN (lower N application: 270 kg N ha−1), and CN (conventional N application: 330 kg N ha−1), and three topdressing distances of LN (LND), e.g., 15 cm (LND1), 30 cm (LND2) and 45 cm (LND3) from maize rows were evaluated. At the beginning seed stage (R5), the leghemoglobin content and nitrogenase activity of LND3 were 1.86 mg plant−1 and 0.14 mL h−1 plant−1, and those of LND1 and LND2 were increased by 31.4 and 24.5%, 6.4 and 32.9% compared with LND3, respectively. The ureide content and N accumulation of soybean organs in LND1 and LND2 were higher than those of LND3. The N uptake, NUE and N agronomy efficiency (NAE) of IMS under CN were 308.3 kg ha−1, 28.5%, and 5.7 kg grain kg−1 N, respectively; however, those of LN were significantly increased by 12.4, 72.5, and 51.6% compared with CN, respectively. The total yield in LND1 and LND2 was increased by 12.3 and 8.3% compared with CN, respectively. Those results suggested that LN with distances of 15–30 cm from the topdressing strip to the maize row was optimal in maize-soybean intercropping. Lower N input with an optimized fertilization location for IMS increased N fixation and N use efficiency without decreasing grain yield.